Pre-Weaning Exposure to Maternal High-Fat Diet Is a Critical Developmental Window for Programming the Metabolic System of Offspring in Mice - Yang, Hong; Chen, Nan; Fan, Lei; Lin, Xiaojing; Liu, Juncheng; You, Yuehua; Zhong, Ying; Chen, Yan; Li, Jibin; Xiao, Xiaoqiu (Frontiers in Endocrinology, 2022)
Background Maternal high-fat diet (HFD) during pregnancy and lactation exerts long-term effects on the health of offspring. However, the critical developmental window for metabolic programming of maternal exposure to HFD on pathogenesis of obesity in offspring needs further clarification. Materials & Methods Female ICR mice were fed low-fat diet (LFD) or HFD for 8 weeks until delivery. During lactation, half of LFD dams received HFD while the other half of LFD dams and HFD dams maintained the previous diet. Male offspring were weaned at postnatal day 21 (P21) and fed LFD or HFD for 7 weeks. Metabolic parameters, biochemical, and histological indicators of thermogenesis, rectal temperature, and sympathetic nerve tone were detected at P21 and 10 weeks old. Results At P21, LH (maternal LFD before delivery but HFD during lactation) and HH (maternal HFD before delivery and during lactation) offspring gained more body weight and showed higher serum glucose and triglyceride levels as compared with LL (maternal LFD before delivery and during lactation), and the metabolic characters were maintained until 10 weeks age when fed with LFD after weaning. However, LH offspring exhibited a greater degree of metabolic abnormalities compared to HH offspring, with increased body weight, as well as lower norepinephrine (NE)-stimulated rectal temperature rise when fed with HFD after weaning. The lower UCP1 levels and HSL phosphorylation in LH offspring further suggested that brown adipose tissue (BAT) thermogenic function was impaired. Conclusion Exposure to maternal HFD feeding during pre-weaning period alone showed similar detrimental effects on programming metabolic system of offspring as those of both prenatal and early postnatal HFD feeding. Early postnatal stage is a critical time window for metabolic programming and has profound and long-lasting effects on BAT development and function through sympathetic nerve-mediated thermogenesis.